A single application of cold atmospheric plasma (CAP) improves blood flow parameters in chronic wounds. (7th March 2022) - Schleusser, Sophie; Schulz, Lysann; Song, Jungin; Deichmann, Henriette; Griesmann, Anna‐Catharina; Stang, Felix H.; Mailaender, Peter; Kraemer, Robert; Kleemann, Markus; Kisch, Tobias
Abstract: Objective: To find out whether application of cold atmospheric plasma (CAP) affects microcirculation in chronic wounds. Methods: We treated 20 patients with chronic wounds on the lower extremity with CAP. Blood flow parameters of wounds were assessed with combined Laser‐Doppler‐Flowmetry and spectrophotometry in tissue depth of 2 and 6–8 mm. Parameters were assessed under standardized conditions before and over the course of 30 min after application of CAP. Results: Deep capillary blood flow increased significantly by up to 24.33% (percentage change) after treatment with CAP and remained significantly elevated until the end of measuring period at 30 min. Superficial oxygen tissue saturation was significantly elevated by 14.05% for the first 5 min after treatment. Postcapillary venous filling pressure was significantly elevated by 10.23% 19 min after CAP and stayed significantly elevated starting from minute 24 until the end of measuring. Conclusion: Cold atmospheric plasma increases microcirculation parameters in chronic wounds significantly. As CAP is known for its benefits in wound healing, the effects observed may explain the improved healing of chronic wounds after its use. Whether CAP‐application can increase blood flow in chronic wounds for longer periods of time or boosts blood flow when applied more than once should be subject to further research.